2020
DOI: 10.3748/wjg.v26.i27.3952
|View full text |Cite
|
Sign up to set email alerts
|

Serum ceruloplasmin can predict liver fibrosis in hepatitis B virus-infected patients

Abstract: BACKGROUND The presence of significant liver fibrosis in hepatitis B virus (HBV)-infected individuals with persistently normal serum alanine aminotransferase (PNALT) levels is a strong indicator for initiating antiviral therapy. Serum ceruloplasmin (CP) is negatively correlated with liver fibrosis in HBV-infected individuals. AIM To examine the potential value of serum CP and develop a noninvasive index including CP to assess significant fibrosis among HBV-infected indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Tan et al [ 22 ] have shown that in patients with CHB, CER levels correlated with the liver fibrosis degree, which was of great value in diagnosing CHB cirrhosis. Kang et al [ 23 ] showed that patients with HBV infection have a negative correlation between CER and liver fibrosis. Significant fibrosis, advanced fibrosis, and liver cirrhosis were all predicted by CER with AUCs of 0.774, 0.812, and 0.853, respectively, which were similar to the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Tan et al [ 22 ] have shown that in patients with CHB, CER levels correlated with the liver fibrosis degree, which was of great value in diagnosing CHB cirrhosis. Kang et al [ 23 ] showed that patients with HBV infection have a negative correlation between CER and liver fibrosis. Significant fibrosis, advanced fibrosis, and liver cirrhosis were all predicted by CER with AUCs of 0.774, 0.812, and 0.853, respectively, which were similar to the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…CP also serves as a ferroxidase that oxidizes ferrous iron to ferric iron for further incorporation into transferrin ( 15 ). Despite the important diagnostic value in Wilson's disease, some studies suggested serum CP was inversely correlated to fibrosis or positively associated with steatosis in hepatitis B patients ( 16 , 17 ). And another study enrolled 100 children with biopsy-proven NAFLD demonstrated that CP had an accuracy of 82% in distinguishing pediatric patients with NAS score ≥ 5 from those with NAS score < 5 ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…A noninvasive model composed of PT, AST, GGT, and anti-hepatitis B core antibody levels is valuable in predicting significant liver inflammation in CHB patients [ 28 ], however, it ignores the fibrosis stage. Conversely, another noninvasive model called CPHBV could accurately predict liver fibrosis in CHB patients with normal ALT level, regardless of liver inflammation [ 29 ]. AGH model composed of AST, hepatitis B core antigen and GGT is a reliable index to predict moderate to severe inflammation or significant fibrosis, which helps to determine the initiation of antiviral therapy [ 30 ].…”
Section: Discussionmentioning
confidence: 99%